Background cortisol versus social anxiety as correlates of HPA-axis recovery from stress in boys with Autism Spectrum Disorder. Issue 71 (December 2018) - Bitsika, Vicki; Sharpley, Christopher F.; McMillan, Mary E.; Agnew, Linda L.
Highlights: Cortisol responses in children with ASD are often dysregulated. Stress response, and recovery from stress, were investigated in boys with ASD. About half the sample demonstrated HPA axis dysregulation. One aspect of Social Phobia was found to significantly correlate with recovery from stress. Abstract: Children with Autism Spectrum Disorder (ASD) show dysregulation of the expected Hypothalamus-Pituitary-Adrenal (HPA) axis and elevated cortisol responses to stress and response patterns, but little has been reported regarding their recovery from stress in terms of cortisol concentrations. This response was investigated in a sample of 32 young males with ASD aged between 9 and 18 years ( M  = 14.3 yr, SD = 2.7 yr), using a standardised experimental protocol combined with individualised stressor and non-stressor tasks. Results indicated that about half of the sample demonstrated unexpected HPA axis response patterns, and that recovery from stress cortisol concentrations were significantly associated with a single symptom of Social Phobia and Morning cortisol. These findings suggest that one of the key diagnostic criteria for ASD may be strongly influential in the HPA axis responses of boys with ASD and that training regimesto assist them to form less fearful associations with their non-ASD peers may be central to the academic and social progress of these boys.